Dom Krestianina. "Der Tierarzt erklärt am Skelett eines Cochsenhäufige Krankheiten der Zügtiere" - Strassberg, ...,
Dom Krestianina. "Der Tierarzt erklärt am Skelett eines Cochsenhäufige Krankheiten der Zügtiere".